Experimenting with social norms : fairness and punishment in cross-cultural perspective - Ensminger, Jean; Henrich, Joseph Patrick (Russell Sage Foundation, 2014)
"Informed by a pioneering set of cross-cultural data, Experimenting with Social Norms, advances our understanding of the evolution of human cooperation and the expansion of complex societies. Innovative and ambitious, the book synthesizes and unprecedent analysis of social behavior from an immense range of human societies."